2017
DOI: 10.3168/jds.2016-11745
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Escherichia coli O157:H7 and bacterial diversity in corn silage contaminated with the pathogen and treated with chemical or microbial additives

Abstract: Inhibiting the growth of Escherichia coli O157:H7 (EC) in feeds may prevent the transmission or cycling of the pathogen on farms. The first objective of this study was to examine if addition of propionic acid or microbial inoculants would inhibit the growth of EC during ensiling, at silo opening, or after aerobic exposure. The second objective was to examine how additives affected the bacterial community composition in corn silage. Corn forage was harvested at approximately 35% dry matter, chopped to a theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 77 publications
6
64
2
Order By: Relevance
“…The high bacterial composition and diversity of AZS and AS during the entire fermentation process ( Table 3 ) contrasts with the previously reported lower values for maize and other crops silages, as the result of a low pH and 80–95% of relative abundance of the Lactobacillus genus [ 23 , 27 , 28 , 29 , 30 , 33 ], but similar to the high values of diversity obtained from the silages of alfalfa, maize from Iran [ 26 , 33 ], and other fermentative processes. Although the AS and AZS had a low pH in all evaluations, the lower relative abundance of Lactobacillus in AS and AZS (0.3–44.5%) reflects that other members of the microbial community were involved in this process, likely as a result of the type of maize, stage of maturity at harvest, local conditions during crop growth or climate [ 52 ].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…The high bacterial composition and diversity of AZS and AS during the entire fermentation process ( Table 3 ) contrasts with the previously reported lower values for maize and other crops silages, as the result of a low pH and 80–95% of relative abundance of the Lactobacillus genus [ 23 , 27 , 28 , 29 , 30 , 33 ], but similar to the high values of diversity obtained from the silages of alfalfa, maize from Iran [ 26 , 33 ], and other fermentative processes. Although the AS and AZS had a low pH in all evaluations, the lower relative abundance of Lactobacillus in AS and AZS (0.3–44.5%) reflects that other members of the microbial community were involved in this process, likely as a result of the type of maize, stage of maturity at harvest, local conditions during crop growth or climate [ 52 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Data from NGS studies on different crop silages have shown a wide view of the silage microbial composition and dynamics [ 26 , 29 , 30 ]. Thus, in the present study, the bacterial community associated with the maize silage process of a forage Mexican landrace and a commercial hybrid, both commonly used in the Los Altos region, Jalisco, were surveyed by a massive high-throughput sequencing approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the high-throughput sequencing method has opened a new way to explore complex microbial ecosystems, and this technique has been widely applied across a range of systems. As reported with this technique to investigate the bacterial diversity of the day 120 corn silage samples 25 . Sufficient data are not yet available on the bacterial community dynamics involved in corn stover ensiling.…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are found in a variety of animal feeds including concentrates, green forests, hay and silages (OGUNADE et al, 2017). Naturally, there are more than 400 mycotoxins, but only a few have been widely studied (NJUMBE et al, 2015).…”
Section: Introductionmentioning
confidence: 99%